An intensive exercise program improves motor performances in patients with dementia: translational model of geriatric rehabilitation - Schwenk, Michael; Dutzi, Ilona; Englert, Stefan; Micol, William; Najafi, Bijan; Mohler, Jane; Hauer, Klaus (Journal of Alzheimer's disease, 2014)
Background: Translation of intensive exercise programs developed specifically for patients with dementia into clinical settings is lacking. Objective: To determine if a progressive resistance and functional training program, previously evaluated in d